Effect of Hoodia Gordonii meal supplementation at finisher stage on productivity and carcass characteristics of Ross 308 broiler chickens - Mohlapo, Teboho Daniel (University of Limpopo, 2009)
Two experiments were conducted to evaluate the effect of Hoodia gordonii meal supplementation at finisher stage on productivity and carcass characteristics of Ross 308 broiler chickens. Experiment 1 examined the effect of levels of Hoodia gordonii meal supplementation of grower diet fed to Ross 308 broiler chickens at the finisher stage (30 – 42 days of age) on productivity and carcass characteristics in a 12 day experimental period. The experiment was a completely randomized design with a 2 (two sexes of chickens) x 6 (levels of Hoodia gordonii meal [0, 100, 200, 300, 400 or 500 mg]) factorial arrangement of treatments in which three hundred and sixty broiler chickens at finisher stage were randomly allocated to twelve treatments with three replicates of ten birds each. Level of Hoodia gordonii meal supplementation had no effect (P>0.05) on diet intake, intake as percentage of live weight, growth rate, feed conversion ratio, live weight at 42 days of age and mortality of broiler chickens at finisher stage. All carcass characteristics were not affected (P>0.05) by the treatments except fat pads. Chickens given a daily dose of 300 mg of Hoodia gordonii meal had lower (P<0.05) fat pad weights than unsupplemented ones. Male broiler chickens had higher (P<0.05) feed intake and heavier drum sticks than female broiler chickens. Experiment 2 examined the effect of Hoodia gordonii meal dose interval at finisher stage in a 2 (two sexes of chickens) x 3 (dosage intervals) factorial, complete randomized design that involved three hundred and sixty chickens that were randomly allocated to six treatments with six replicates of ten birds each. Broiler chickens were fed either a grower diet without Hoodia gordonii meal; grower diet with 300 mg of Hoodia gordonii meal/ bird supplemented everyday for 12 days; or grower diet with 300 mg of Hoodia gordonii meal/ bird supplemented twice, on 30th and 36th days of age. Hoodia gordonii meal dose interval had no effect (P>0.05) on dry matter feed intake, intake as percentage of live weight, growth rate, live weight at 42 days of age, feed conversion ratio, mortality and all carcass characteristics except fat pad of broiler chickens. Daily dosing with 300 mg of Hoodia gordonii meal/ bird reduced (P<0.05) fat pad weights of broiler chickens by 18 percentage points. Male broiler chickens had higher (P<0.05) feed intake, nitrogen digestibility, nitrogen retention and live weight than female broiler chickens. It is concluded that chickens given a daily supplement of 300 mg of Hoodia gordonii meal had lower fat pad weights than unsupplemented ones. This could not be explained in terms of differences in feed intake, digestibility, or growth rate.
Thesis (Bsc. (Animal production)) --University of Limpopo, 2009.
Keywords: Hoodia Gordonii; Broilers; 636.5108842; Broilers (Chickens); Chickens -- Breeding